Spinodal decomposition during isothermal gas-solid equilibration – Its effects and implications. (December 2018) - Sasidhar, K.N.; Meka, S.R.
Abstract: The possibility for a system to sample non-classical chemical pathways while attempting to attain thermodynamic equilibrium under conditions of restricted kinetics has been elucidated in this work through the analogy of gas phase nitriding of iron based alloys. Detailed thermodynamic assessment has for the first time shown evidence for the occurrence of in-situ isothermal spinodal decomposition during controlled nitridation of ferritic Fe-Cr alloys. Recognition of this phenomenon has led to the explanation of certain reported anomalous experimental observations: dependence of nitridation kinetics of ferritic Fe-Cr alloys on N diffusion and the paradox of Cr-nitrides precipitation sequence not following the predictions of the phase diagram in nitrided Fe-Cr alloys. Finally, the nitridation kinetics of Fe-Al alloys being controlled by Al diffusion has been attributed to the absence of a possibility for spinodal decomposition during nitriding of Fe-Al alloys. Graphical abstract: Image 1